PENGARUH FAKTOR KEPERILAKUAN ORGANISASI PADA IMPLEMENTASI SISTEM INFORMASI KEUANGAN DAERAH (Studi Empiris Pada Pemerintah Daerah Kabupaten Karanganyar) - Fakultas EkonomiUniversitas Sebelas Maret, Yati (MAJALAH ILMIAH GEMA, 2014)
A Local Information Financial System (SIKD) can give a better information for strategically decision making in particular related to transparency and accountability in public sector, this research aim to verify the influence Local Information Financial System (SIKD) implementation factor  that supported, clarity purpose and training by usefulness of SIKD.This population research are civil servants in management of funds department, heading department of funds and the staff of it in all SKPD local goverment of Karanganyar regency. Technique determination of samples by using census method, samples which are taken a number of 17 SKPD. The analysis of hypothesis testing are used SPSS 16.  The result indicated that clarity purpose had a positive effect on SIKD. the training had an effect on it, and supported had a positive effect too an it. This research results supporty chenhall (2004) research that declared of ABCM usability of planning product related to the success of financial. This research suggested in order that in the implementation system behold another behavioral factor in innovation system.  Key word: Clarity of aim, training, boss support, SIKD.